IMPLEMENTASI PEMBERDAYAAN MASYARAKAT PADA PROGRAM DESA KELURAHAN SIAGA AKTIF DI KABUPATEN WAJO - Abdul Kadir; Abdul Muhaimin Taiyeb (Andragogi Kesehatan BBPK Makassar, 2022)
ABSTRACTThe aim of the study was to analyze the implementation of community empowerment to alert village program in Wajo regency. The study was qualitative using a phenomenological approach. The study was conducted at Tonralipue village, Tanasitolo district and Sanreseng Ade village, Bola district, Wajo regency. The selection of the location was done by stratified purposive sampling. The data were analyzed qualitatively. The results of the study indicate that Desa / Kelurahan Siaga is known as a village in which the community is able to identify, formulate, and fid solution to health problems, and make use of potential resource owned. The empowerment of community is the form of meeting, self alertness, discussion, observation of simple epidemiology and family of nutritional awareness.Keywords : community empowerment, desa /kelurahan siaga aktif, family of nutritional awareness ABSTRAKTujuan Penelitian ini adalah untuk menganalisis pelaksanaan pemberdayaan masyarakat pada program desa dan kelurahan siaga aktif di Kabupaten Wajo. Disain penelitian adalah pendekatan kualitatif untuk memperoleh informasi secara mendalam tentang pelaksanaan pemberdayaan masyarakat pada program desa dan kelurahan siaga aktif. Lokasi penelitian di desa Tonralipue kecamatan Tanasitolo dan desa Sanreseng Ade Kecamatan Bola Kabupaten Wajo yang dipilih secara stratified purposive